2016
DOI: 10.1016/j.radcr.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Transient washout of hepatic hemangiomas: Potential pitfall mimicking malignancy

Abstract: Hemangiomas are the most common tumor of the liver and distinguishing them from malignancy is important. This is a report of 3 hemangiomas in 2 patients that exhibit transient washout of gadoxetate disodium (Eovist), relative to blood pool and liver parenchyma, a characteristic that is used to diagnose hepatocellular carcinoma in at-risk patients. It is important to recognize that high-flow hemangiomas can exhibit transient washout when using a small volume of injected contrast agent. This finding is unlikely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, the T1‐weighted fat‐saturated post‐contrast MR images from the standard MR‐enterography protocol were used for the analysis in the present study 22 . The administered amount of the gadolinium‐based contrast was weight dependent and because skeletal muscle signal intensity of back muscles is relative stable during different contrast phases, the post‐contrast phase of the T1‐weighted images will not influence our results on skeletal muscle signal intensity 25 . The border of cerebrospinal fluid is harder to visualize on T1‐weighted images compared to T2‐weigthed images; therefore, the cerebrospinal fluid was demarked by a standardized square of nine pixels.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the T1‐weighted fat‐saturated post‐contrast MR images from the standard MR‐enterography protocol were used for the analysis in the present study 22 . The administered amount of the gadolinium‐based contrast was weight dependent and because skeletal muscle signal intensity of back muscles is relative stable during different contrast phases, the post‐contrast phase of the T1‐weighted images will not influence our results on skeletal muscle signal intensity 25 . The border of cerebrospinal fluid is harder to visualize on T1‐weighted images compared to T2‐weigthed images; therefore, the cerebrospinal fluid was demarked by a standardized square of nine pixels.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, HH appears on scans as one or more clear nodules with low density on CT. After injecting contrast agents, an enhancement is present in nodule peripheral and homogeneous centripetal filling [ 8 ]. A rapid enhancement of hepatic artery and transient washout show a relatively high specificity with the diagnosis of HCC [ 9 ]. However, previous studies showed low sensitivity (almost 50%) especially for the lesion's diameter smaller than 1 cm [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alpha fetoprotein (AFP), the most remarkable diagnostic serological marker, could also be at high levels in acute hepatitis, cirrhosis, colitis, etc. These lead to the challenges of the precise diagnosis of small-size HH or HCC [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%